Sabilulungan as local wisdom value sustainability plan after the change of leadership in Bandung Regency - Budiana, Heru Ryanto; Sjafirah, Nuryah Asri; Dipa, Adzkia Kirana (Universitas Padjadjaran, 2022)
The leadership of the Regent Dadang Mochamad Naser for two periods, namely the first period in 2010-2015 and the second period in 2016-2021, used the value of local wisdom “Sabilulungan.” Each leader will have a new leadership style in carrying out the organization’s activities. The value of Sabilulungan’s local wisdom as a spirit in carrying out the wheels of development in Bandung Regency has led Bandung Regency to accelerate development in all fields. It has attracted the attention of researchers to examine in more depth the plan for the sustainability of the implementation of the value of Sabilulungan local wisdom in the implementation of public services after the change of leadership. This research approach is a qualitative approach using a case study method. The research paradigm used is the constructivism paradigm. The results of this study found that the leadership change in Bandung Regency adopted and modified the Sabilulungan values that had been applied to the previous leadership. The renewal and improvement of the vision and mission of Sabilulungan to Bedas is an attempt to continue development in Bandung Regency. Leadership changes occurred, but the value of the local wisdom of Sabilulungan will remain eternal as a cultural value for the people of Bandung Regency. The change of value in the new vision and mission to Sabilulungan, which has been with the people of Bandung for a decade, will require a communication effort that starts from scratch. It is necessary to manage the delivery of value messages and media management that is planned and measurable so that the Bedas value can be accepted as an updated value in Bandung Regency.